The impact of differential payroll tax subsidies on minimum wage employment - Kramarz, Francis,Philippon, Thomas (IZA, 2000)
In this article, we study the impact of changes of total labor costs on employment of low-wage workers in France in a period, 1990 to 1998, that saw sudden and large changes in these costs. We use longitudinal data from the French Labor Force survey (
Keywords: Arbeitspapier; Graue Literatur; Niedriglohn; Arbeitskosten; Gewerbesteuer; Lohnsubvention; Frankreich